Fetal Origin of Placental Hepatic Nodule. (December 2021) - Bu, Fang; Pfau, Ruthann; Deeg, Carol; Wobser, Jeff; Koo, Selene C.
Intraplacental hepatic nodules are extremely rare and range from incidentally identified microscopic nodules to large mass-forming lesions. We describe the case of an incidentally identified intraparenchymal hepatic nodule in the placenta from a near-term delivery of a male infant at 36 weeks gestation. Lesional cells were positive for HepPar1, focally positive for glypican3, and negative for calretinin and alpha-fetoprotein, supportive of hepatocellular origin. Fluorescence in-situ hybridization and chromosomal microarray both showed a male sex chromosome complement (XY) within the nodule, confirming the fetal origin of this nodule. We provide the first report of the confirmed fetal origin of these rare lesions, lending support to the hypothesis that placental hepatic nodules may represent an embryonal rest or residua of abnormal cell migration.